2006
DOI: 10.1080/09712119.2006.9706819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molasses and Sulphuric Acid Addition to Barley/Hungarian Vetch Bi-Crop Silages

Abstract: Bingol, N.T., Karsli, M.A., Bolat, D. and Akca, I. 2006. Effect of molasses and sulphuric acid addition to barleymungarian vetch bi-crop silages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…There were significantly higher LA content and lower pH in molasses‐added silages than in control. This could be ascribed to molasses directly providing more fermentation substrates for LAB, and enhanced LA fermentation (Bingol et al, 2006). Several researches have demonstrated that 4% molasses performed best (Guo et al, 2014), and the fermentation quality may not be remarkably improved by adding molasses less than 3% (Latif et al, 2015), while bad fermentation may occur when adding molasses in high content, because excessive soluble carbohydrates may be used by undesirable bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…There were significantly higher LA content and lower pH in molasses‐added silages than in control. This could be ascribed to molasses directly providing more fermentation substrates for LAB, and enhanced LA fermentation (Bingol et al, 2006). Several researches have demonstrated that 4% molasses performed best (Guo et al, 2014), and the fermentation quality may not be remarkably improved by adding molasses less than 3% (Latif et al, 2015), while bad fermentation may occur when adding molasses in high content, because excessive soluble carbohydrates may be used by undesirable bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…One of the biggest problems of the livestock sector is insufficient production of roughage, in terms of both quantity and quality, which should be included in the rations of ruminant animals (Bingöl et al,2010). In order to minimize the quality roughage needs for livestock enterprises, forage crop production areas should be increased, meadow and pasture qualities should be improved, especially cheap and alternative roughage sources (pulp) should be brought into animal production and quality roughage production techniques should be transferred to breeders.…”
Section: Introductionmentioning
confidence: 99%